PENGARUH MEDIA E-LEARNING DAN MOTIVASI BELAJAR TERHADAP IPK AKADEMIK MAHASISWA STKIP PANCA SAKTI - Nadia Rista (Universitas Indraprasta PGRI, 2021)
The purpose of the research is to examine the level of positive and significant (1) influence e-learning media to GPA of students in economic educationt program study year 2019/2020 in STKIP Panca Sakti, (2) influence learning motivation to academic GPA of students in economic educationt program study year 2019/2020 in STKIP Panca Sakti. The population of the research is students at economic educationt program study year 2019/2020 that amounts 697 students. The sampling technique used is the propotional random sampling, wich then obtained a sample of 255 students. Method of collecting data by using documentation and questionnaire. Data analysis method used descriptive analysis and multiple regression analysis.The result showed that (1) e-learning media significantly influence to academic GPA of students in economic educationt program study year 2019/2020 in STKIP Panca Sakti, (2) learning motivation significantly influence to academic GPA of students in economic educationt program study year 2019/2020 in STKIP Panca Sakti.